Tropical fruits and other edible plants of the world : an illustrated guide - Blancke, Rolf (Comstock Publishing Associates, a division of Cornell University Press, 2016)
"Illustrated with photographs taken on location in the plants' natural environment, this field guide describes more than three hundred species of tropical and subtropical species of fruits, tubers, and spices"--Resumé vydavatele
"A Zona Tropical publication."--Titulní strana
Terminologický slovník
Keywords: tropické ovoce; tropické užitkové rostliny; tropické rostliny; tropical fruit; tropical crops; tropical plants; příručky; handbooks and manuals